Comparison of recycled vapor contribution to precipitation in urban vs. rural area—A case study in western China - Zhao, Pei; Xia, Chengcheng; Liu, Guodong; Tang, Jialiang; Zhou, Minghua (Frontiers in Ecology and Evolution, 2023)
While urbanization’s strong effect on local precipitation has been widely documented, knowledge of how urbanization affects isotopic composition in precipitation is still lacking. In the present study, deuterium-excess (d-excess) served to quantify the contribution of recycled vapor to precipitation in Chengdu city (China) and a nearby rural area. Precipitation from the urban and rural areas sampled showed no significant difference in δ18O values (p > 0.05). The rural area had significantly higher d-excess (24.29 ‰ ± 7.39 ‰) than the urban (12.71 ‰ ± 4.88 ‰) through the seasons due to higher evapotranspiration flux in the rural area. In summer, however, urban precipitation amount was higher than that of the rural area (p = 0.065). Based on d-excess model, the average ratio of recycled vapor was 8.2 % in Chengdu which was lower than Jieliu (36.1 %). This highlights the effect of urbanization in decreasing the proportion of vapor from local evapotranspiration contributing to precipitation but blocked much advected moisture. This also implied that precipitation taken in cities were used to represent upwind advected vapor or used to compare isotopic series of tree rings or stalagmites sampled in rural area may be erroneous as the effect of urbanization on precipitation vapor. Further studies are needed to explore the effect of urbanization on vapor source of precipitation.